2008
DOI: 10.1177/0306624x08323454
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of Sex Offender Social Policies and the Impact on Sex Offenders

Abstract: This study examines the public perception of sex offender policies and the perceived impact of sex offender policies on the sex offenders themselves. Specifically, this study explores how the community feels about the effectiveness of policies such as registration and community notification (Megan's Law), and housing restrictions in reducing sexual recidivism. Data are collected from 115 participants from a nationwide online community message board. Results suggest that although most individuals support Megan'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 16 publications
6
86
0
Order By: Relevance
“…For example, in the survey by Levenson and colleagues (2007), 83% of community members agreed that community notification is effective in reducing sex offenses, 74% agreed that adult sex offenders go on to commit other sex offenses, and 68% agreed that they are much more likely to reoffend than are other criminals. Schiavone and Jeglic (2008) reported that, of those surveyed, 65% agreed that communities are safer when they know where sex offenders live and 44% agreed that registration and community notification prevent offending (although 57% did not believe that registration laws affect the rate of recidivism among sex offenders). In reality, compared with offenders who commit nonsexual crimes, sex offenders are less likely to commit nonsexual offenses and only slightly more likely to commit another sex offense (U.S. Department of Justice, 2007).…”
Section: Studymentioning
confidence: 99%
“…For example, in the survey by Levenson and colleagues (2007), 83% of community members agreed that community notification is effective in reducing sex offenses, 74% agreed that adult sex offenders go on to commit other sex offenses, and 68% agreed that they are much more likely to reoffend than are other criminals. Schiavone and Jeglic (2008) reported that, of those surveyed, 65% agreed that communities are safer when they know where sex offenders live and 44% agreed that registration and community notification prevent offending (although 57% did not believe that registration laws affect the rate of recidivism among sex offenders). In reality, compared with offenders who commit nonsexual crimes, sex offenders are less likely to commit nonsexual offenses and only slightly more likely to commit another sex offense (U.S. Department of Justice, 2007).…”
Section: Studymentioning
confidence: 99%
“…When asked to write in the number of years they believed sex offenders should spend in prison, the majority of participants answered "99," the highest number that would fi t in the response section. Community and political support is notoriously high for all of the aforementioned sex offender policies, even in the face of mounting evidence of their ineffectiveness and unsubstantiated cost (Griffi n & West, 2006 ;Schiavone & Jeglic, 2009 ).…”
Section: Incapacitationmentioning
confidence: 99%
“…infl uence legislation often leads to crime-control efforts that are based more in fear than in fact and that are ineffective as a result (Armstrong, Miller, & Griffi n, 2015 ;Schiavone & Jeglic, 2009 ).…”
mentioning
confidence: 99%
“…A possible explanation as to why homeless shelters have such a policy is that sex offender laws are in place to prevent sex offenders from reoffending. These laws are based on lawmakers' and the public's perception of sex offenders' potential to reoffend (Kernsmith et al, 2009;Schiavone & Jeglic, 2009). Lawmakers are held accountable as to which policies are implemented in order to protect their constituents from sex offenders (Sample & Kadleck, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the jurisdiction, the sex offender could be prohibited from residential units within 500 to 2,500 feet from schools, preschools, daycares, playgrounds, parks, and/or any other community structures where children congregate deemed necessary by policymakers within the state and/or local jurisdiction (Neito & Jung, 2006). The consequences of these residency restriction laws have been serious and long lasting for the registrants, as well as the communities in which they live (Burchfield & Mingus, 2008;Harris, Lobanov-Rostovsky & Levenson, 2010;Kernsmith, Craun & Foster, 2009;Levenson, 2008;Levenson & Cotter, 2005a, 2005bMustaine, 2014;Mustaine, Tewksbury & Stengel, 2006b;Ragusa-Saleno & Zgoba, 2012;Schiavone & Jeglic, 2009;Tewksbury, 2005;Willis & Grace, 2009). …”
Section: Chapter II Review Of the Literaturementioning
confidence: 99%